Rational Pricing of Internet Companies Operating in Emerging Market - Lau, Yue Ming Alan (2008)
Tradition discounting cash flows (DCF) technique no doubt is a handy and useful tool for managers to valuate projects on hand or values of companies. Yet, due to its inborn insufficiencies and not practical assumptions, the usefulness of conventional DCF approach would seem limited when capturing the value of managerial flexibilities. In the current dynamic business world, uncertainties constitute a large part of companiesÃÂÃÂ¢ÃÂÃÂÃÂÃÂ value, especially of those in internet industry. Hence, the value would be hugely underestimated under the DCF valuation and would suggest wrong decisions to managers and calculate incorrect values of companies.